Libraries and Information Services and the Content Analysis Method in Scientific Literature Produced in the Areas of Librarianship and Information Sciences in Mexico. - Cardenas, Celia Mireles (Qualitative and Quantitative Methods in Libraries, 2017)
Information Services is defined as the activities carried out informative institutions to meet the information needs of its users. As the diversity of users and information services provided by libraries presents a variety of shapes and designs, so finding methodologies for understanding the current and prospective situation in which they find these services, essential. This article studies the cases, manner of application, and results obtained from utilizing the content analysis method in the postgraduate theses carried out in the area of Librarianship and Information Sciences in Mexico.